Administering a SQL database infrastructure exam 70-764 certification training : prepare for the Microsoft 70-764 exam and work towards your MCSA: SQL 2016 database administration certification - Long, Mark (O'Reilly, 2017)
"The course prepares you to take Microsoft exam 70-764, the first of two tests you must pass in order to earn the Microsoft Certified Solutions Associate (MCSA): SQL 2016 Database Administration certification. Passing the 70-764 exam indicates to the world that you have what it takes to administer the SQL database infrastructure."--Resource description page.
Title from title screen (Safari, viewed July 5, 2017). - Release date from resource description page (Safari, viewed July 5, 2017)
Keywords: SQL server -- Study guides -- Examinations; Computer networks -- Study guides -- Management -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Microsoft software -- Study guides -- Examinations; Database management; SQL server; Réseaux d'ordinateurs; Gestion; Examens; Guides de l'étudiant; Logiciels Microsoft; Examens; Guides de l'étudiant; Bases de données; Gestion; Computer networks; Management; Examinations; Electronic data processing personnel; Certification; Examinations; Microsoft software; Examinations; Study guides